The Effect of Financial Literacy and Financial Inclusion on Retirement Planning - Rahmat Aryo Baskoro; Rensi Aulia (International Journal of Business Economics (IJBE), 2019)
This study aims to determine the effect of financial literacy and financial inclusion on retirement planning. This study used a quantitative method with 236 respondents and processed by the method of multiple linear regression analysis. The results of the study show that financial literacy and financial inclusion have a significant effect on retirement planning, means that the higher financial literacy and financial inclusion of a person, the better their retirement planning. In addition, the results of the study showed that respondents were dominated by moderate financial literacy levels with a percentage of 55.08%, moderate financial inclusion levels with a percentage of 57.20% and high retirement planning levels with presentations of 52.54% of the total respondents. Researchers also conduct additional research by choosing one of the demographic factors, which is monthly income. The results that monthly earnings also influence retirement planning where the higher a person's monthly income, the better their retirement planning